Complement Receptor 1 availability on red blood cell surface modulates Plasmodium vivax invasion of human reticulocytes (2019)
Plasmodium vivax parasites preferentially invade reticulocyte cells in a multistep process that is still poorly understood. In this study, we used ex vivo invasion assays and population genetic analyses to investigate the involvement of complement receptor 1 (CR1) in P. vivax invasion. First, we observed that P. vivax invasion of reticulocytes was consistently reduced when CR1 surface expression was reduced through enzymatic cleavage, in the presence of naturally low-CR1-expressing cells compared with high-CR1-expressing cells, and with the addition of soluble CR1, a known inhibitor of P. falciparum invasion. Immuno-precipitation experiments with P. vivax Reticulocyte Binding Proteins showed no evidence of complex formation. In addition, analysis of CR1 genetic data for worldwide human populations with different exposure to malaria parasites show significantly higher frequency of CR1 alleles associated with low receptor expression on the surface of RBCs and higher linkage disequilibrium in human populations exposed to P. vivax malaria compared with unexposed populations. These results are consistent with a positive selection of low-CR1-expressing alleles in vivax-endemic areas. Collectively, our findings demonstrate that CR1 availability on the surface of RBCs modulates P. vivax invasion. The identification of new molecular interactions is crucial to guiding the rational development of new therapeutic interventions against vivax malaria. © 2019, The Author(s).